Kinetics of formation and dissociation of gas hydrates. (October 2017) - Manakov, Andrey Yu.; Penkov, Nikita V.; Rodionova, Tatyana V.; Nesterov, Anatoliy N.; Fesenko, Evgeny E.
Abstract : The review covers a wide range of issues related to the nucleation, growth and dissociation of gas hydrates. The attention is focused on publications of the last 10 – 15 years. Along with the mathematical models used to describe these processes, the results of relevant experimental studies are surveyed. Particular sections are devoted to the gas hydrate self-preservation effect, the water memory effect in the hydrate formation, development of catalysts for hydrate formation and the effect of substances dissolved in the aqueous phase on the formation of hydrates. The main experimental techniques used to study gas hydrates are briefly considered. The bibliography includes 230 references.